(3eONd Edi GdMQjGJ h Mbhb GdEfSGf (B:s (3GdLRA GdChd aj GdfXQjI GdYGeI ddMQjGJ h Mbhb GdEfSGf (B/s - (3Hf NQa Gddg, GdWGgQs ((3GdLRGFQ (B:s (3WGcSjL che ,s, 2007)
(3jJfGhd GdcGJH JWhQ GdMQjGJ h Mbhb GdEfSGf ef ShahcdjS Gdi GdbGfhf GdhVYj edQhQG HYOI eMWGJ acQjI h eOGQS ePgHjI Jhej GdEchfj eOQSI GdbGfhf GdWHjYj h GdHTQ eOQSI GdYbO GdGLJeGYj Ke GdePGgH GdhVYjI GeG eUGOQ GdMQjGJ h Mbhb GdEfSGf ajJfGhdgG ef eUGOQg GdKdGKI GdOGNdjI Gh GdeUOQ GdhWfj GdOhdjI h GdOjfjI h jSJYQV HGdTQM eMJhjGJ gPg GdeUGOQ eY GdebGQfI HHYV GdfeGPL GdCLfHjI h aj GNQ GdJMdjd jSJYQV GdcGJH Gge GdGfJbGOGJ GdJj hLgJ deNJda GdGdjGJ GdOhdjI GdeJHYI aj GdOaGY Yf Mbhb GdEfSGfs
Keywords: (3GdMQjGJ GdYGeIs; (3GdMQjIs